Potential Combination of Phytoremediation Plants and Compost in Remediation of Hg in Ex-Gold Mine Soil Contaminated Mercury (Hg) - Amri, Amarrusli Ali; Fauzi, Taufik; Sudharmawan, A. A. Ketut; Mulyati, Mulyati; Suwardji, Suwardji (Jurnal Biologi Tropis, 2024)
Heavy metal mercury pollution in the environment can have negative impacts on both surrounding ecosystems and human health. Sources of mercury pollution often come from mining activities, particularly from many unlicensed gold mines (PETI) that use the mercury amalgamation method to extract gold. Due to the persistent, bioaccumulative, and toxic nature of mercury, contamination in the soil has increased. One effort to reduce mercury toxicity is the application of absorption methods using phytoremediation plants and compost as regulating factors. The aim of this study is to review sources of information related to the use of phytoremediation plants and the application of compost as remediators to clean mercury (Hg)-contaminated soil. To reduce levels of heavy metal contamination, plants employ five phytoremediation mechanisms: phytoextraction, phytostabilization, rhizofiltration, phyto degradation, and phytovolatilization. Therefore, selecting hyperaccumulator plants that have the ability to accumulate mercury (Hg) at levels 100 times higher than ordinary plants is crucial for effective remediation. Additionally, the use of compost as a source of organic material can enhance mercury mobility. The addition of organic materials such as compost can increase C organic content, cation exchange capacity (CEC), pH, and Hg-chelate formation, thereby maximizing mercury absorption by plants. This combination has a positive impact on reducing mercury levels in the soil and is environmentally safe.